A STUDY ON EDUCATION FOR REFUGEES: WHICH MODEL WORKS BEST FOR MALAYSIA? - Abu Bakar, Norani; Subramaniam, Thirunaukarasu (SARJANA, 2024)
In 2021, Malaysia achieved impressive completion rates of 99.8% for lower secondary education and 97.8% for upper secondary education. However, only 4% of marginalized non-citizen children are enrolled in primary education, and just 16% in secondary education. These figures are significantly lower than global refugee enrolment rates, which are 68% for primary and 37% for secondary education. Given the global resettlement rate that is below 1%, it is crucial for Malaysia to increase refugee learners’ enrolment in education programs. This study employs a systematic literature review to compare education models from six other refugee-hosting countries - Bangladesh, Thailand, Indonesia, Turkey, Jordan, and Lebanon - to identify the most effective education model for refugees in Malaysia. The findings uncovered that there is no universal approach as different models are effective at varying context and time frame. The literature review also reveals coherent views on Alternative Learning Centre model as the most appropriate framework for Malaysia’s current context. However, given the prolonged stay of refugees, the paper argues for gradual integration into the national education system. Hence, the recommendations address models relevant to both scenarios, operationalizing them by leveraging accessible resources through their socio-ecological system.